Sensory Substitution: The Spatial Updating of Auditory Scenes “Mimics” the Spatial Updating of Visual Scenes - Pasqualotto, Achille; Esenkaya, Tayfun (Frontiers in Behavioral Neuroscience, 2016)
Visual-to-auditory sensory substitution is used to convey visual information through audition, and it was initially created to compensate for blindness; it consists of software converting the visual images captured by a video-camera into the equivalent auditory images, or ‘soundscapes’. Here, it was used by blindfolded sighted participants to learn the spatial position of simple shapes depicted in images arranged on the floor. Very few studies have used sensory substitution to investigate spatial representation, while it has been widely used to investigate object recognition. Additionally, with sensory substitution we could study the performance of participants actively exploring the environment through audition, rather than passively localising sound sources. Blindfolded participants egocentrically learnt the position of six images by using sensory substitution and then a judgement of relative direction task (JRD) was used to determine how this scene was represented. This task consists of imagining being in a given location, oriented in a given direction, and pointing towards the required image. Before performing the JRD task, participants explored a map that provided allocentric information about the scene. Although spatial exploration was egocentric, surprisingly we found that performance in the JRD task was better for allocentric perspectives. This suggests that the egocentric representation of the scene was updated. This result is in line with previous studies using visual and somatosensory scenes, thus supporting the notion that different sensory modalities produce equivalent spatial representation(s). Moreover, our results have practical implications to improve training methods with sensory substitution devices.